Learning Climate and Job Performance among Health Workers. A Pilot Study - Cortini, Michela; Pivetti, Monica; Cervai, Sara (Frontiers in Psychology, 2016)
This paper will explore if and how psychological strain plays a mediator role between the learning climate and job performance in a group of health workers. Although the relationship between learning climate and job performance has already been explored in the international literature, the role of psychological strain, which may hamper or deepen this relationship, has yet to be investigated. The research hypothesis is that psychological strain mediates the relationship between the climate towards learning (including also the error avoidance climate) and job performance. Data were gathered in a Public hospital in Italy. Participants (N = 61) were health professionals (nurses and obstetricians). Considering the relatively small sample size, a mediation analysis with the aid of the SPSS macro PROCESS was performed. The results show that the relationship between the learning climate (specifically its dimension of organizational appreciation towards learning) and job performance is mediated by psychological strain. The future research agenda and practical implications are discussed in the paper.